Christian Ethics Regarding Cryptocurrency Investment - Styadi Senjaya; Ferry Simanjuntak (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2022)
Cryptocurrency is a digital currency that utilizes blockchain technology to do investments. This study aims to provide answers for Christians on how to respond to Cryptocurrency investments from the perspective of Christian ethics. The research method used is through the library research approach. This study indicates that cryptocurrency itself as a new technology is an agnostic technology; rather, it is the attitude and motivation of a person that determines the suitability of cryptocurrency in a particular situation. Thus, pastors and believers can invest in cryptocurrency, depending on their motivations.